Mass transfer operations for the practicing engineer - Theodore, Louis; Ricci, Francesco (Hoboken, N.J. : Wiley, 2010)
"Part of the Essential Engineering Calculations Series, this book presents step-by-step solutions of the basic principles of mass transfer operations, including sample problems and solutions and their applications, such as distillation, absorption, and stripping. Presenting the subject from a strictly pragmatic point of view, providing both the principles of mass transfer operations and their applications, with clear instructions on how to carry out the basic calculations needed, the book also covers topics useful for readers taking their professional exams"--
"The book is divided into three parts: Introduction, Applications, and Other Topics. The first part provides a series of chapters concerned with principles that are required when solving most engineering problems, including those in mass transfer operations. The second part deals exclusively with specific mass transfer operations, e.g., distillation, absorption and stripping, adsorption, etc. The last part provides an overview of ABET (Accreditation Board for Engineering and Technology) related topics as they apply to mass transfer operations, plus novel mass transfer processes"--
Frontmatter -- Introduction. Part Introduction -- History of Chemical Engineering and Mass Transfer Operations -- Transport Phenomena vs Unit Operations Approach -- Basic Calculations -- Process Variables -- Equilibrium vs Rate Considerations -- Phase Equilibrium Principles -- Rate Principles -- Applications: Component and Phase Separation Processes. Part Introduction -- Introduction to Mass Transfer Operations -- Distillation -- Absorption and Stripping -- Adsorption -- Liquid²́⁶Liquid and Solid²́⁶Liquid Extraction -- Humidification and Drying -- Crystallization -- Membrane Separation Processes -- Phase Separation Equipment -- Other Topics. Part Introduction -- Other and Novel Separation Processes -- Economics and Finance -- Numerical Methods -- Open-Ended Problems -- Ethics -- Environmental Management and Safety Issues -- Appendix A: Units -- Appendix B: Miscellaneous Tables -- Appendix C: Steam Tables -- Index.
Includes bibliographical references and index.
Print version record.
Keywords: Engineering mathematics; Mass transfer; SCIENCE -- Energy; SCIENCE -- Mechanics -- General; SCIENCE -- Physics -- General; Engineering mathematics; Mass transfer; Electronic books; Electronic books